Understanding the experiential intersections of violence, gender identities and mental health, in the accounts of male parolees, in Gauteng, South Africa - Kallenbach, Jessica Jade (University of the Witwatersrand, Johannesburg, 2023)
Imprisonment in South Africa has been categorized by untold hardships and suffering. Some of the major factors which influence life in correctional centres in South Africa, are embedded within violence, gender identities and mental health. These three constructs – violence, gender identities and mental health – appear embedded within the logic of the correctional centre regime. Thus, to understand the entirety of an offender’s experience during incarceration, it is necessary to investigate the intersections of violence, gender identities and mental health. This was achieved using a qualitative hermeneutic phenomenological approach to centre on the participants’ experiences. This research consisted of six semi-structured face-to-face interviews with male parolees at Zonderwater Correctional Community Centre. The interviews were based on a self-developed questions derived from research by Akhona (2014), Bantjes et al. (2017), Celinska and Sung (2014) and Gear and Ngubeni (2002). The interview questions were open-ended and focused on the participants’ subjective meanings, understandings and experiences regarding the dynamic intersection of violence, gender identities and mental health in South African correctional centres. The findings of this research revealed that the exposure to and involvement in violent acts are inextricably related to the fundamental deprivations that offenders are subjected to and the associated “pains of imprisonment”. This revelation demonstrated the negotiation of gender that takes place within these confines, making acts of sexual assault and violence deemed more acceptable. In navigating this system of violence and gender identity negotiations, the findings of this study illustrated the emotional and mental impact that this environment has on offenders. This highlighted the pertinent need for the Department of Correctional Centres (DCS) to address current gaps in the rehabilitation models they use. These gaps could account for the recidivism rate in South Africa. It is clear that the intersection of violence, gender identities and mental health play an influential role in determining the reported experiences of offenders. The study thus has the potential to contribute to policies, by illustrating that a multi-layered approach to rehabilitation is required.
A research project submitted in partial fulfilment of the requirements for the degree of Masters of Arts (Social and Psychological Research), in the field of Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 15 March, 2023.
Keywords: Correctional centre; Gender identities; Male parolees; Mental health; South Africa; Violence; SDG-3: Good health and well-being